Frequency of Anemia in Patients with Newly Diagnosed Pulmonary Tuberculosis Presenting at Dr Ruth KM Pfau Civil Hospital Karachi - Sana Muhammad Hussain; Amanullah Abbasi; Bader Faiyaz Zuberi; Anoshia (JLUMHS)
OBJECTIVE: To determine the frequency of anemia in patients with newly diagnosed pulmonary Tuberculosis (PTB) presenting at Dr Ruth K M Pfau Civil Hospital Karachi (CHK). METHODOLOGY: This cross-sectional study was conducted at Dr Ruth KM Pfau CHK from July to August 2023. Newly diagnosed pulmonary tuberculosis cases of either gender, between 14-40 years, were included, while patients with a history of PTB, malnutrition, blood loss, HIV, pregnant females, autoimmune disorders, anemia before the diagnosis of PTB, chronic illness and malignancies were excluded. PTB patients were labeled anemic if the hemoglobin level was <13g/dl in males and <12g/dl in females. Quantitative and qualitative variables were presented as descriptive statistics, giving mean, standard deviation, and frequency and percentages. Correlation and regression analysis of hemoglobin with age, gender and employment status was done. A P-value of ≤0.05 as significant. RESULTS: Out of 150 patients, 91(60.7%) were male and 59(39.3%) were female. The frequency of anemia in males and females was 55.4% and 44.6%, respectively, which was not statistically significant (p = .865). A strong positive correlation of anemia with increasing age, with the highest frequency of anemia at 66.8% in age groups of >38 years compared to 6.8% in the 18-30 age group (p <.001) was present. Regression analysis showed age, gender and employment status were responsible for a 29.4% change in hemoglobin levels. CONCLUSION: Anemia is common in patients with PTB and more common in patients with advancing age. Females had lower hemoglobin levels than males in PTB patients.